2022
DOI: 10.1084/jem.20212307
|View full text |Cite
|
Sign up to set email alerts
|

Delineating a serotonin 1B receptor circuit for appetite suppression in mice

Abstract: Triptans are a class of commonly prescribed antimigraine drugs. Here, we report a previously unrecognized role for them to suppress appetite in mice. In particular, frovatriptan treatment reduces food intake and body weight in diet-induced obese mice. Moreover, the anorectic effect depends on the serotonin (5-HT) 1B receptor (Htr1b). By ablating Htr1b in four different brain regions, we demonstrate that Htr1b engages in spatiotemporally segregated neural pathways to regulate postnatal growth and food intake. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…However, although 5‐HT 1B R is also coupled to G i/o proteins, 12 5‐HT 1B R knockout mice have increased bodyweight with increased food and water intake, 71 suggesting an anorexigenic role of 5‐HT 1B Rs. These findings are well‐explained by results from previous studies showing that the arcuate NPY/AgRP neurons express 5‐HT 1B R 64 and that 5‐HT 1B R stimulations inhibit NPY/AgRP neurons to decrease food intake 64,72 (Table 1). Inhibition of NPY/AgRP neurons also decreases the inhibitory synaptic inputs to POMC neurons, which should further the anorexigenic effects 64 .…”
Section: Regulation Of Appetitesupporting
confidence: 80%
See 2 more Smart Citations
“…However, although 5‐HT 1B R is also coupled to G i/o proteins, 12 5‐HT 1B R knockout mice have increased bodyweight with increased food and water intake, 71 suggesting an anorexigenic role of 5‐HT 1B Rs. These findings are well‐explained by results from previous studies showing that the arcuate NPY/AgRP neurons express 5‐HT 1B R 64 and that 5‐HT 1B R stimulations inhibit NPY/AgRP neurons to decrease food intake 64,72 (Table 1). Inhibition of NPY/AgRP neurons also decreases the inhibitory synaptic inputs to POMC neurons, which should further the anorexigenic effects 64 .…”
Section: Regulation Of Appetitesupporting
confidence: 80%
“…Therefore, it appears that the anorexigenic effects produced by the inhibition of arcuate NPY/AgRP neurons by 5‐HT 1B Rs are significantly larger than possible orexigenic effects that may result from the inhibition of DRN/MRN serotonergic neurons. Consistent with this idea, a recent study demonstrated that systemic administrations of antimigraine drugs target 5‐HT 1B Rs expressed by the NPY/AgRP neurons to decrease food intake 72 (Table 1).…”
Section: Regulation Of Appetitementioning
confidence: 61%
See 1 more Smart Citation
“…In contrast to the limited ARC innervation, DRN SERT neurons project heavily to some of the brain areas also innervated by AgRP projections. Notably, we found that CP94253 directly inhibited synaptic currents elicited by AgRP axons in LH and PVN [ 49 ], suggesting Gi-coupled 5HT1B-R on AgRP neurons directly inhibit output at presynaptic level ( Figure S7 ). Thus, serotonergic input from DRN and potentially from other sources may also alter target neuronal activity through modulation of release from AgRP axon terminals.…”
Section: Discussionmentioning
confidence: 99%